Contribution of Ezrin on the Cell Surface Plasma Membrane Localization of Programmed Cell Death Ligand-1 in Human Choriocarcinoma JEG-3 Cells - Mayuka Tameishi; Takuro Kobori; Chihiro Tanaka; Yoko Urashima; Takuya Ito; Tokio Obata (MDPI AG, 2021)
Immune checkpoint blockade (ICB) antibodies targeting programmed cell death ligand-1 (PD-L1) and programmed cell death-1 (PD-1) have improved survival in patients with conventional single agent chemotherapy-resistant gestational trophoblastic neoplasia (GTN). However, many patients are resistant to ICB therapy, the mechanisms of which are poorly understood. Unraveling the regulatory mechanism for PD-L1 expression may provide a new strategy to improve ICB therapy in patients with GTN. Here, we investigated whether the ezrin/radixin/moesin (ERM) family, i.e., a group of scaffold proteins that crosslink actin cytoskeletons with several plasma membrane proteins, plays a role in the regulation of PD-L1 expression using JEG-3 cells, a representative human choriocarcinoma cell line. Our results demonstrate mRNA and protein expressions of ezrin, radixin, and PD-L1, as well as their colocalization in the plasma membrane. Intriguingly, immunoprecipitation experiments revealed that PD-L1 interacted with both ezrin and radixin and the actin cytoskeleton. Moreover, gene silencing of ezrin but not radixin strongly diminished the cell surface expression of PD-L1 without altering the mRNA level. These results indicate that ezrin may contribute to the cell surface localization of PD-L1 as a scaffold protein in JEG-3 cells, highlighting a potential therapeutic target to improve the current ICB therapy in GTN.